MATHEMATICAL MODEL OF A THERMOELECTRIC SEMICONDUCTOR SYSTEM FOR VISUALIZING THE TEMPERATURE FIELDS OF OBJECTS - O. V. Evdulov; R. A. Magomadov; K. A. Magomedova; E. A. Dzhabrailova (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objective. The research objective is to develop a mathematical model of a thermoelectric semiconductor system to visualize the temperature fields of objects and study the thermophysical internal processes. Methods. A thermoelectric semiconductor system was developed for visualizing the temperature fields of flat objects using a liquid crystal film. Its feature is to increase the accuracy of measurements due to a more accurate coupling of the object and the device. A mathematical simulation of  the system was performed based on the solution of a dynamic two- dimensional heat conduction problem with local heat sources and sinks over  the area of a liquid crystal film. Results. Dependency graphs were obtained for the dependency of two-dimensional temperature distribution over the surface of the liquid crystal film in the presence of heat sources and sinks, the change in the cooling capacity, the cooling ratio, the supply voltage of the thermoelectric module on the temperature difference between the junctions for different  values of the supply current. Conclusion. As a result of calculations, it was found that the color gamut of a liquid crystal film changed significantly in the presence of heat sources and sinks on its surface. During pre-calibration, the system allows visualization  of the object temperature field and determines the value of its temperature at each point. Following the calculated data, it is determined that to ensure  the entire operation of the thermoelectric semiconductor system, a standard thermoelectric module ICE-71 can be used with the following specifications: power range – 16 to 35 W with an average temperature difference between the junctions – 55 K, the supply current – 28 A with a power consumption of 40 to 90 W, the cooling ratio is from 0.38 to 0.43.